The current status of psychological birth trauma in women who had a vaginal delivery and associated factors: a questionnaire-based, cross-sectional study - Qin, Hong; Wei, Weiwei; Feng, Xiaoyan; Yang, Xiaochang (Frontiers in Public Health, 2025)
ObjectiveIndividuals vary in their perception of psychological birth trauma (PBT), with some individuals progressing to postpartum post-traumatic stress disorder (PP-PTSD). However, from both preventive and developmental perspectives, PBT and PP-PTSD have received limited attention in China. This study examines the prevalence and influencing factors of PBT among women who underwent vaginal delivery in Chongqing, China, at 3 days and 42 days postpartum, as well as the correlation between perceived PP-PTSD and PBT, aiming to enhance understanding in this field.MethodsThis questionnaire-based, cross-sectional study was conducted on women who had a vaginal delivery admitted to a grade III-A general hospital using convenience sampling between February and April of 2024. Participants were questioned using a general questionnaire, the Birth Trauma Perception Scale for Women During Vaginal Delivery (BTPS-WVD) scale, and the Postpartum Post-Traumatic Stress Disorder Scale (PP-PTSD) at 3 and 42 days postpartum. Univariate and multiple linear regression analysis was performed to identify factors associated with PBT at 42 days postpartum. Pearson correlation analysis was used to investigate the correlation between PBT and PP-PTSD in women who had a vaginal delivery.ResultsThe average score of PBT at 3 and 42 days postpartum were (43.37 ± 9.46) and (51.40 ± 13.54) respectively, the difference was statistically significant (p < 0.05). There were statistically significant differences in the dimensions of medical support trauma perception, delivery pain trauma perception, family support trauma perception, and delivery outcome trauma perception (p < 0.05). The average score of PP-PTSD at 3 and 42 days postpartum were (22.38 ± 7.13) and (22.29 ± 5.77) respectively, with no statistical significance (p > 0.05). The positive rate of PP-PTSD (score ≥ 38) at 3 and 42 days postpartum were 5 and 2%, respectively. Univariate analysis showed that, feeding mode, the effect of breast swelling on mood, mother separate from the newborn, separation time between mother and newborn, place of puerperium, psychological discomfort caused by delivering with others, use of epidural anesthesia, delivery time, advise others to deliver vaginally, the effects of wound pain, time of the postnatal wound pain and who decides on abnormal delivery were independently associated with PBT (p < 0.05). Multiple linear regression analysis showed that, mother separate from the newborn, separation time between mother and newborn, place of puerperium, psychological discomfort caused by delivering with others, the effects of wound pain, time of wound pain, who decides on abnormal delivery were independently associated with PBT (p < 0.05). Pearson correlation analysis showed that, PBT and its four dimensions were positively correlated with PP-PTSD (r = 0.488, p < 0.001).ConclusionWomen who experienced PBT during vaginal delivery reported significantly higher levels of perceived trauma at 42 days postpartum compared to 3 days postpartum. Clinical staff, family, and society should pay attention to the risk factors and take corresponding intervention measures to reduce the degree of PBT and promote maternal and child health.